Production Response of Athulya Layer Chicken to Dietary Energy Concentration and Feed Particle Size - Chacko, Binoj; P., Anitha (International Journal of Livestock Research, 2021)
An experiment was carried out in 450 Athulya layer hens (commercial strain cross of Single Combed White Leghorn) from 17 to 64 weeks of age to evaluate the influence of metabolizable energy (ME) levels (2200, 2400 and 2600 kcal/kg) and feed particle size (3.0, 5.0 and 7.0 mm) on production performance and economics in a 3x3 factorial design. All experimental diets were identical in calorie protein ratio. The results revealed statistically similar housed egg production and egg weight were observed among treatments. The daily feed intake and feed conversion ratio (FCR) value was significantly (p<0.001) lower in birds fed diet with 2600 kcal/kg ME than in birds fed diet with lower ME levels (2400 and 2200 kcal/kg). Particle size did not influence feed intake and FCR. The body weight and body weight gain at 40 and 64 weeks of age was significantly (p<0.05) higher in 2600 kcal/kg ME group than in lower ME levels (2400 and 2200 kcal/kg) group. The different particle size did not affect body weight and body weight gain at 40 and 64 weeks of age. Livability of birds was not influenced by either dietary ME levels or particle size. The highest return over feed cost per egg was recorded in birds fed 2200 kcal/kg ME diet with particle size of 7.0 mm. Thus, the results of present study indicated that diet containing ME level of 2200 kcal/kg with 15.22 per cent CP and particle size of 7.0 mm was most suitable for Athulya layer chicken from 17 to 64 weeks of age.